Jovens que cantam em bando: uma prática interdisciplinar e contemporânea de canto coral em Caxias do Sul - Ferronato, Cristiane (My University, 2020)
Based on my observation of a contemporary youth choir practice I analyse in this dissertation whether Art may constitute itself as a reflexive and interdisciplinary tool in Education and, in particular, for the expansion of historical awareness, potentializing a citizenly existence. In the search for answers I investigate the processes of composition, conceptualization and execution of the “Contrapontos” performance by the Moinho UCS Youth Choir, beyond the relevance of the historical context under which it was conceived. Art, Education and collective vocal practice, particularly, are discussed here as the development of the human on becoming in view of a contemporary and interdisciplinary experience of youth choir singing connected to a multifaceted formation in artistry, dialoguing with possibilities of transcreations. I seek to prove these premises from the analysis of the singers' reports and from the testimonies of professionals participating in the performance, which also resulted in the product of this research, the documentary “Stories Artisting Mills”. Sewing meanings among theories from different authors, such as Gilles Deleuze and Felix Guattari, Ernani Maletta, Roberto Crema, Sandra Mara Corazza, Murray Schafer, Howard Gardner, José D´Assumpção Barros and Jörn Rüsen, who support this work, I present some concepts like: polyphonic rhizome, self-tuning, normosis and historical awareness, weaving ideas that may serve as input and inspiration for professionals from different areas of knowledge.
Nesta dissertação, analiso, a partir da observação de uma prática coral juvenil contemporânea, se a Arte pode se constituir como ferramenta reflexiva e interdisciplinar na Educação e, em especial, para a ampliação da consciência histórica, potencializando uma existência cidadã. Na busca por respostas, investigo os processos de composição, conceituação e execução do espetáculo Contrapontos pelo o Coro Juvenil do Moinho/UCS, além do contexto histórico sob o qual o projeto foi concebido, e sua relevância. A Arte, a Educação e especialmente a prática vocal coletiva são discutidas aqui como um devir para o desenvolvimento humano, tendo em vista uma vivência contemporânea e interdisciplinar de canto coral juvenil, conectada a uma formação multifacetada em artistamentos, dialogando com possibilidades de transcriações. Busco a comprovação dessas premissas a partir da análise de relatos dos cantores e de depoimentos de profissionais participantes do espetáculo, registros que também originaram a criação do documentário “Moinhos Artistadores de Histórias”, produto desta pesquisa. Costurando sentidos entre teorias de diversos autores que fundamentam este trabalho, como Gilles Deleuze e Felix Guattari, Ernani Maletta, Roberto Crema, Sandra Mara Corazza, Murray Schafer, Howard Gardner, José D´Assumpção Barros e Jörn Rüsen, apresento alguns conceitos como: rizoma polifônico, afinação de si, normose e consciência histórica, tecendo ideias que poderão servir de aporte e inspiração para profissionais de distintas áreas do conhecimento.
Keywords: História - Estudo e ensino; Canto coral infanto-juvenil; Canto coral - Caxias do Sul; History - Study and teaching; Children's choir singing; Coral Corner -Caxias do Sul (Brazil)